Authorship in Medical Literature - Parajuli, Ramesh (Nepalese Journal of ENT Head and Neck Surgery, 2017)
Scientific paper publication has an important role in the academic filed. Being an author of such paper based on the research or other scholarly activity is associated with many benefits such as peer recognition, financial gain, promotion, job appointment, and fellowship and research awards. The race to increase the quantity rather than the quality of manuscript among the researchers has made the researchers being involved in an unethical practice. To be included as an author one must fulfill the authorship criteria developed by the International Committee of Medical Journal Editors (ICMJE). One shouldn’t be given credit for authorship who can’t defend the published work. Authorship misuse in the form of gift authorship, guest authorship or ghost authorship is not uncommon these days. To reduce the authorship conflicts many journals have set strict policy to mention about the nature of the contribution made by each “author” and that information is available to the readers.